2021
DOI: 10.1073/pnas.2110601118
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic regulation of axonal Kv1.1 channels accounts for both synaptic and intrinsic modifications in the hippocampal CA3 circuit

Abstract: Homeostatic plasticity of intrinsic excitability goes hand in hand with homeostatic plasticity of synaptic transmission. However, the mechanisms linking the two forms of homeostatic regulation have not been identified so far. Using electrophysiological, imaging, and immunohistochemical techniques, we show here that blockade of excitatory synaptic receptors for 2 to 3 d induces an up-regulation of both synaptic transmission at CA3–CA3 connections and intrinsic excitability of CA3 pyramidal neurons. Intrinsic pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 79 publications
1
22
0
Order By: Relevance
“…This mechanism is further supported by the genetic deletion of LGI1, which decreases both Kv1.1 channel density and D-type currents by more than 50% [ 16 ]. As Kv1.1 channels are expressed at both the AIS and presynaptic terminals of CA3 pyramidal neurons [ 17 ], the putative consequence of the decrease in Kv1.1-mediated current is an elevated neuronal excitability and an elevated glutamate release, which both concur to promote synchronous epileptiform discharges. Our results were obtained in vitro, as most results describing the effects of LGI1 manipulation on neuronal excitability.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism is further supported by the genetic deletion of LGI1, which decreases both Kv1.1 channel density and D-type currents by more than 50% [ 16 ]. As Kv1.1 channels are expressed at both the AIS and presynaptic terminals of CA3 pyramidal neurons [ 17 ], the putative consequence of the decrease in Kv1.1-mediated current is an elevated neuronal excitability and an elevated glutamate release, which both concur to promote synchronous epileptiform discharges. Our results were obtained in vitro, as most results describing the effects of LGI1 manipulation on neuronal excitability.…”
Section: Discussionmentioning
confidence: 99%
“…Kv1 channels are not only located at the AIS where they determine intrinsic excitability but they are also located at presynaptic terminals where they sharpen the spike and reduce transmitter release (Kole et al, 2007; Boudkkazi et al, 2011; Zbili et al, 2021). Interestingly, the up-regulation of intrinsic neuronal activity in KO-Lgi1 CA3 pyramidal cells comes with a loss of Kv1 channel function at the presynaptic terminal (Seagar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our data demonstrate that LGI1 determines intrinsic excitability by controlling the expression of Kv1.1 channels at the AIS. Kv1 channels are not only located at the AIS where they determine intrinsic excitability but they are also located at presynaptic terminals where they sharpen the spike and reduce transmitter release (Kole et al, 2007;Boudkkazi et al, 2011;Zbili et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This makes one wonder why LAR would require homeostatic control in the first place. Kv1.1 is implicated with rapid, <10 min, homeostatic regulation of hippocampal excitability 27,28 . Recently, it has been shown that LAR can be flexibly controlled in timeframes <10 min, suppressing the LAR completely by sensitising a threat memory 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Kv1.1 has been recently shown to be involved in the homeostatic control of firing 27,28 through modulation of the axon initial segment (AIS) 29 . Thus, our behavioural and physiological results isolate a key molecular player in Setd5, Kv1.1, that causes the physiological hypoexcitability phenotype, probably arising through homeostatic misregulation, either by localisation 27 , posttranslational modifications 30 or interactions with auxiliary subunits 31 . current injection.…”
Section: Hypoexcitability In Dpag Neurons Is Due To Kv Misregulationmentioning
confidence: 99%